NARASI NASIONALISME SENTRIPETAL DALAM NOVEL PEMENANG SAYEMBARA “SEBERAPA INDONESIAKAH DIRIMU?” (Centripetal Nationalism In Contest Winners Novel Winners of Seberapa Indonesiakah Dirimu?) - Candra Rahma Wijaya Putra; Purwati Anggraini; Joko Widodo (Kandai, 2021)
This study aims to describe the direction of nationalism narrated in the three winning novels of the contest “How Indonesia Are You?”. This type of research is descriptive qualitative using a post-colonial perspective. The data sources used are the novel Because I'm Not Blind by Redy Ugeng Kuswanto, Kaki Langit Talumae by Wishnu Mahendra, and the novel How to Love Indonesia by Dumamilanta S. Brahmana. The research data are in the form of words, phrases, sentences, or paragraphs that narrate the concept of the nation and the form of nationalism. The results of this study indicate that 1) the three novels describe the construction of the nation as a community with a collective consciousness in the form of history, customs, and natural resources; 2) nation construction contains problematization. The nation is vaguely divided into traditional and modern spaces resulting in social inequality; and 3) Overall the three novels want the integration of locality in nationalism. Thus, the direction of nationalism narrated in the three novels is centripetal nationalism. The direction of centripetal nationalism is believed to be a solution in overcoming the problem of nationalism.Penelitian ini bertujuan untuk mendeskripsikan arah nasionalisme yang dinarasikan dalam tiga novel pemenang Sayembara “Seberapa Indonesiakah Dirimu?”. Jenis penelitian ini adalah deskriptif kualitatif dengan menggunakan perspektif pascakolonialisme. Sumber data yang digunakan adalah novel Karena Aku Tak Buta karya Redy Ugeng Kuswanto, Kaki Langit Talumae karya Wishnu Mahendra, dan novel How to Love Indonesia karya Dumamilanta S. Brahmana. Data penelitian berupa kata, frasa, kalimat, atau paragaraf yang menarasikan konsep bangsa dan bentuk nasionalisme. Hasil penelitian ini menunjukan bahwa 1) ketiga novel menggambarkan konstruksi bangsa sebagai komunitas dengan kesadaran kolektif berupa sejarah, adat istiadat, dan sumber alam; 2) konstruksi bangsa mengandung problematisasi. Bangsa secara samar terpecah dalam ruang tradisional dan modern yang mengakibatkan ketimpangan sosial; dan 3) Secara keseluruhan ketiga novel menginginkan intregasi lokalitas dalam nasionalisme. Dengan demikian, arah nasionalisme yang dinarasikan di dalam ketiga novel adalah nasionalisme sentripetal. Arah nasionalisme sentripetal diyakini menjadi solusi dalam mengatasi problematisasi kebangsaan.